Optimalisasi Standardisasi Produk, Inovasi Kemasan, dan Pemasaran Digital dalam Mewujudkan UMKM yang Berkelanjutan - Fisla Wirda; Herizon Herizon; Trimardi Jayaputra; Ariani Tanjung; Deni Wahyuni (Lembaga Komunitas Informasi Teknologi Aceh (KITA), Indonesia, 2026)
Kerupuk Azizah is a micro, small, and medium enterprise (MSME) with an average production capacity of 200 kg per day and employing 30 workers. However, the partner faced several challenges, including a consignment-based sales system with payment claim periods of up to three months, stagnant revenue due to products reaching the maturity stage of the market, limited marketing coverage predominantly within Padang City, and the use of simple packaging that lacked nutritional information and barcode labeling. This community service activity aimed to enhance production capacity and business management through product standardization, packaging innovation, and digital marketing implementation. The implementation methods included training and mentoring in both production and management aspects. The production aspect involved nutritional composition testing for three product types, namely garlic crackers, purple sweet potato crackers, and shrimp crackers, as well as the development of new packaging designs and barcode labeling. The management aspect included training on social media utilization, digital marketing through marketplaces, and live streaming product promotion. The results showed that the partner successfully obtained nutritional composition test certificates for three products from the Food Standardization and Industrial Quality Assurance Agency, developed one new packaging design equipped with nutritional information and barcode, and expanded digital marketing utilization through four media platforms, namely Facebook, Instagram, Shopee, and TikTok. This activity contributed to improving product quality, expanding marketing reach, and strengthening the sustainability of the partner’s business.